The real cyber war : the political economy of internet freedom - Powers, Shawn M., 1981-; Jablonski, Michael (Urbana : University of Illinois Press, 2015)
"Cyber war is on the rise. For many, cyber war refers to the extension of military strategy and conflict into electronic networks, or more simply, the use of the internet for various forms of covert, forceful attack. In The Real Cyber War: The Political Economy of Internet Freedom, Shawn M. Powers and Michael Jablonski argue that, beyond covert attacks, cyber war refers to the utilization of the electronic networks for geopolitical purposes, and the internet, and the rules that govern it, can shape political opinions, consumer habits, cultural mores and values. Powers and Jablonski outline the historical genesis of the internet freedom movement, tracing its origins to modern day. Moving beyond debates about the democratic value of new and emerging media technologies, they focus on political, economic, and geopolitical factors driving internet freedom policies, with particular focus on the U.S. policy and the State Department's emerging doctrine in support of a universal freedom to connect. Far from a principled defense of the freedom of expression, this analysis reveals how internet governance and infrastructure have emerged as critical sites for geopolitical contest between major international actors, the results of which will shape 21st century statecraft, diplomacy, and conflict"--
Introduction : geopolitics and the Internet -- Information freedom and U.S. foreign policy : a history -- The information industrial complex -- Google, information, and power -- The economics of internet connectivity -- The myth of multistakeholder governance -- States, intranets, and sovereignty -- Internet freedom in a surveillance society.
Includes bibliographical references (pages 209-259) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Internet -- Political aspects; Internet and international relations; Internet governance; Internet -- Government policy -- United States; Internet -- Aspect politique; Internet et relations internationales; Gouvernance d'Internet.; Internet -- Politique gouvernementale -- États-Unis.; BUSINESS & ECONOMICS -- Industries -- Media & Communications Industries; SOCIAL SCIENCE -- Media Studies; POLITICAL SCIENCE -- Economic Conditions; Internet and international relations; Internet governance; Internet -- Government policy; Internet -- Political aspects; United States